2014
DOI: 10.1371/journal.pone.0110301
|View full text |Cite|
|
Sign up to set email alerts
|

Rocky Intertidal Zonation Pattern in Antofagasta, Chile: Invasive Species and Shellfish Gathering

Abstract: BackgroundBiological invasions affecting rocky intertidal zonation patterns, yield information on species interactions. In the Bay of Antofagasta, northern Chile, the non-indigenous tunicate Pyura praeputialis, originally from Australia, has invaded (in the past century or so) and monopolized a major portion of the mid-intertidal rocky shore, displacing upshore the native mussel Perumytilus purpuratus. In Antofagasta the tunicate is subjected to intensive exploitation. Monitoring protocols show that in the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…Sampling sites along the SE shore of the bay were: El Lenguado (23°46′ S; 70°28′ W), south of Coloso Point; MEL, on the shore within the Minera Escondida Limitada facility (23°45′ S; 70°28′ W), at Coloso Point; El Way (23°44′ S; 70°26′ W) and AAA (23°4 2′ S; 70°25′ W), north of Coloso Point. All these sites are open to shellfish gathering and show complete or significant reductions in size of the tunicate aggregations (Castilla et al 2014). On the EC shore of the bay, Trocadero (23°35′ S; 70°23′ W), is a rocky shore next to a remodelled artificial beach that opened to the public in 2012.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sampling sites along the SE shore of the bay were: El Lenguado (23°46′ S; 70°28′ W), south of Coloso Point; MEL, on the shore within the Minera Escondida Limitada facility (23°45′ S; 70°28′ W), at Coloso Point; El Way (23°44′ S; 70°26′ W) and AAA (23°4 2′ S; 70°25′ W), north of Coloso Point. All these sites are open to shellfish gathering and show complete or significant reductions in size of the tunicate aggregations (Castilla et al 2014). On the EC shore of the bay, Trocadero (23°35′ S; 70°23′ W), is a rocky shore next to a remodelled artificial beach that opened to the public in 2012.…”
Section: Methodsmentioning
confidence: 99%
“…At Antofagasta, the species has monopolized a major portion of the mid-intertidal rocky shore, displacing upshore the native dominant mussel P. purpuratus (Castilla et al 2004a). Within this extremely restricted range P. praeputialis plays an important role as a bioengineer species, providing habitat for invertebrates and algae (Cerda & Castilla 2001;Castilla et al 2004b) and as an invertebrate resource, because it is extracted by local rocky shore food-gatherers (Castilla et al 2014). A recent study (Castilla et al 2014) has suggested that along the south-eastern shore of the Bay of Antofagasta (approximately 12 km of coastline) the intertidal aggregations of P. praeputialis have declined notably as a consequence of their intensive and long-term exploitation by rocky shore Pyura gatherers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations